IFN-α-mediated Base Excision Repair Pathway Correlates with Antiviral Response Against Hepatitis B Virus Infection. Issue 1 (December 2017) - Li, Yong; Xia, Yuchen; Han, Meifang; Chen, Guang; Zhang, Dake; Thasler, Wolfgang; Protzer, Ulrike; Ning, Qin
Abstract Previous studies identified APOBEC deaminases as enzymes targeting hepatitis B virus (HBV) DNA in the nucleus thus affecting its persistence. Interferon (IFN)-α treated chimpanzees and hepatitis C patients showed elevated APOBEC expression. We thus hypothesized that the responses to IFN-α treatment of chronic hepatitis B (CHB) patients is influenced by IFN-induced base excision repair (BER). CHB-treatment naïve patients, patients treated with PEGylated IFN-α, and patients with sequential treatment of Entecavior and PEGylated IFN-α were recruited. Blood and liver biopsy samples were collected before treatment and at treatment endpoint. BER genes were assessed by quantitative RT-PCR. BER gene expression levels and IFN treatment responses were correlated in patient liver biopsies. APOBEC3A, -B, -C, -D/E, and-G mRNA levels were up-regulated in IFN-treated patients. APOBEC3A expression was significantly higher in IFN-responders than in non-responders. BER genes NEIL3 was down-regulated in IFN-treated patients. APOBEC3 and BER gene expression at treatment endpoints partially correlated with the corresponding absolute DNA level or degree of HBsAg and HBV DNA decline. Our study suggests that the expression of APOBEC3A positively correlates with IFN-treatment responses in CHB patients, while NEIL3 shows negative correlation. These genes may involve to IFN mediated viral suppression and serve as biomarkers for CHB disease management.